Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Educación Inicial de la Facultad de la Educación, el Arte y la Comunicación, 2023-2024 - Espinoza Elizalde, Shylian Anahy (2024)
The present study had the objective of analyzing the relationship between the levels of the basic cognitive processes of Attention and Memory, and Reading Comprehension in students of the first cycle of the Early Childhood Education course of the Faculty of Education, Art and Communication, 2023-2024. A descriptive, correlational and cross-sectional quantitative approach was adopted, using a non- experimental design. The Attention d2 test, the RIAS subscale, and the (ICLAU) were administered in a sample of 32 students. Spearman's Correlation Coefficient was used. The findings revealed that no significant correlation was found between Attention and Reading Comprehension of +0.16 between the Direct Attention Scores and the Total/ICLAU Scores. In addition, moderate correlations were observed, such as +0.42 between Direct Scores/D2 and Critical Level of Idea Comparison/ICLAU, and +0.40 between Hits/D2 and the same level of ICLAU. Between the General Memory Scale and Total Scores/ICLAU, a moderate correlation of +0.40 was observed. Highlighting a strong correlation of +0.60 between the General Memory Scale/RIAS and the Critical Level of Idea Comparison/ICLAU. Correlations of +0.47 were also found between the General Memory Scale/RIAS and Critical Level of Opinion Justification/ICLAU, and +0.44 between the Verbal Memory subtest/RIAS and Total Scores/ICLAU. Based on the results, the null hypothesis in Correlation of Attention and Reading Comprehension is accepted, while the alternate hypothesis in Correlation of Memory and Reading Comprehension is accepted.